LEGAL STATUS OF WOMEN-HIGHLANDERS IN THE END OF 1920S – FIRST HALF OF 1930S: EXPECTATIONS AND REALITY - Kajmarazov, Gani Sihvalievic; Kajmarazova, Lejla Ganievna (History, Archeology and Ethnography of the Caucasus, 2020)
The modern legal status of a Russian woman and the establishment of conditions for achieving equality between men and women have been in the focus of the state and society. In this regard, the study and generalization of the historical experience of gender regulation in Soviet Russia (1917–1991), especially in the late 1920s – early 1930s, is of undoubted scientific and practical interest, by the end of which the authorities announced the solution to the “women’s question”. The issues of the legal status of the Russian women are reflected in works of native, as well as regional and foreign experts. Modern historiographical groundwork, new sources (starting from the normative and record-keeping documents to materials of periodicals and ego-documents), the use of the principle of historicism, systematic and anthropologic approaches, comparative-historical, comparative-legal and descriptive methods allow to reveal the legal status of women-highlanders of Dagestan. The study aims to demonstrate how in the conditions of the polyethnic region the Soviet legislation of the first decades of Soviet power, making adjustments to the rights and obligations of a highland woman who was under the great influence of Islam and the historically established traditions of Dagestan society, changed its position and provided new opportunities for implementation women’s aspirations in everyday, economic, professional, political and cultural life. The paper provides estimations on some “traditional” practices of women, who were discontented with policies carried out by the Soviet power and who organized public marches. As a result of the study, the authors come to the conclusion that the Soviet authorities viewed women as their ally in socialist transformations, and the legal and economic equality of men and women, recorded in Soviet laws, created conditions for the involvement of women in all spheres of life of the Dagestan society. At the same time, during the period under review, the predominance of the traditional form of the family continued to be ensured by the strictest social control.